Defective alloantigen-presenting capacity of 'Langerhans cell histiocytosis cells'. Issue 11 (November 1992) - Yu, R C; Morris, J F; Pritchard, J; Chu, T C
Abstract : The functional activity of skin cells derived from an infant who died of multisystem Langerhans cell histiocytosis (LCH) was examined. Involved and non-involved skin was obtained at postmortem examination within three hours of death; normal epidermal Langerhans cells and 'LCH cells' were separated by means of dispase digestion. The functional activity of different populations of CD1a positive cells was assessed using the conventional six day allogeneic mixed cell reaction. Compared with Langerhans cells from a healthy control, LCH cells showed minimal functional activity. However, Langerhans cells from non-involved skin showed normal and Langerhans cells overlying involved skin showed augmented functional activity. These findings suggest that LCH is a disease in which abnormal Langerhans cells accumulate and/or proliferate in various tissues but it does not affect the entire Langerhans cell population.